Key directions of the scientific, pedagogical and public activity of B. Murzubraimov (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article analyzes the main directions of the scientific, pedagogical, and public activity of the prominent Kyrgyz scholar, Doctor of Chemical Sciences, Professor, and Academician of the National Academy of Sciences of the Kyrgyz Republic, Bektémir Murzubrаimov. A scholarly assessment is provided of the multifaceted professional path of the scientist, his role in establishing ascientific school, his contributions to the development of higher education, his leadership mission in mentoring talented young scholars, and his socio-public position. The article also examines the impact of Murzubrаimov’s work on the development of the national education system.
Keywords: B. Murzubrаimov, academician, personality, science, pedagogical activity, leadership, public activity.